Influence of Broiler Breeder and Laying Hen Breed on the Apparent Metabolizable Energy of Selected Feed Ingredients - Pishnamazi, A.; Pourreza, J.; Edriss, M.A.; Samie, A.H. (International Journal of Poultry Science, 2005)
An experiment was conducted to investigate the effect of genotype (meat-type or egg-type) on the AME digestibility of selected ingredients. The practice of using only one value for apparent metabolizable energy (AME) of feed ingredients for all classes of poultry has been questioned. The ability to convert nutrients to the final products depends on a variety of factors, such as age, sex, genetic and housing system. Some studies have indicated that broiler breeders are less able to metabolize diet energy, than are Leghorn birds. In this study, the ingredients included samples of cereals (corn, wheat and barley), one sample of plant protein (soybean meal) and one cereal by-product (wheat bran). Forty adult males (20 per breed) were randomly assigned to five feedstuffs. Each feedstuff was fed to four birds per breed. The AMEn values were determined using a classical total collection method (Sibbald method). The AME of each feed ingredient was calculated from the difference between GE intake and GE losses in the droppings. The AME values were corrected to zero nitrogen balance (AMEn). The results were showed the average AMEn digestibility in wheat (egg-type : 2785, Kcals/Kg ; meat-type : 2750 Kcals/Kg) and barley (egg-type : 2715 Kcals/Kg; meat-type : 2675 Kcals/Kg) samples were similar in two breeds. The AMEn digestibility in White Leghorn birds was significantly greater for corn (egg-type : 3065 kcals/Kg ; meat-type : 2842 kcals/Kg) , soybean (egg-type : 2185 Kcals/Kg ; meat-type : 2040 Kcals/Kg) and wheat bran (egg-type : 1440 Kcals/Kg ; meat-type : 1333 Kcals/Kg) compared to the broiler strain. In this study, considerable differences were also noted between the two breeds that were tested in their ability to utilize the AME of feed ingredients. In mature broiler breeder hens excess ME intake can cause fat deposition; consequently, accurate representation of the energy content of a breeder diet is important. On the other hand, deficiencies of energy around the time of peak egg production will likely reduce egg production at this time, or production will fall after peak by definition. Since tables concerning ingredient composition usually contain ME values determined with White Leghorn, further research is needed if energy content of broiler breeder diets is accurately represented.